Christology in Digital Era: A Socio-systematic Theology Contribution to the Sustainable Smart Society - Christar Arstilo Rumbay (PASCA : Jurnal Teologi dan Pendidikan Agama Kristen, 2020)
Theology, specifically speaking, Christology, owns exclusive position and tends react sentimentally toward secular disciplines out of its circle. Therefore, linking Christology and digital era falls to practical matter on how modern devices could be employed for religion advantages. This essay tries to evaluate reconciliation between them and see possibilities on how Christology could contribute to the sustainable smart society. However, divinity and technology are contrast square that offers less of space for dialogue, furthermore, it receives pessimistic tone concerning their health relationship. The expectation is, a socio-systematic sensitive approach of Christology may ground new perspective and results unexpected knowledge for the sustainable of smart society.